London in John Sherman: Irish-English Dualism in Early Yeats - Dutta, Ashim (Spectrum, 2025)
W. B. Yeats is mostly known as a poet and a playwright with works spanning from the 1880s to the 1930s. But little attention has been paid to his narrative writing. His only completed novel John Sherman (1891) offers a rather simplistic treatment of the binary between Ireland and England represented by the attitudes of its titular character towards his native Irish town Ballah and the imperial metropolis of London. Despite containing some intriguing autobiographical elements, the novel belies the complex formation of its author’s identity in the late 1880s and the early 1890s, when it was composed and published. By reading the novel in the light of his letters and autobiographical reflections, this essay will highlight the similarities and dissonances between Sherman’s and young Yeats’s attitudes towards London and Englishness. It will demonstrate that, although Yeats chose a rather straightforward nationalist narrative for the novella, he personally took a more ambivalent and nuanced approach to the Irish-English dichotomy, which reveals his personal, familial, and class anxieties. This essay challenges any easy and unambiguous self-other categorization in considering Yeats’s attitude towards London, which is complicated by his reservations about both nationalism and cosmopolitanism. Spectrum, Volume 18, June 2023: 22-30